Avaliação do uso de computação paralela utilizando uma rede P2P na simulação de dados climáticos: velocidade e direção do vento - Serckumecka, Adriano (2012)
The main objective of this work is the evaluation of distributed systems based on peer-topeer network and parallel computing techniques to reduce response times of climate simulations. A probabilistic model for simulating wind data was used and two computing applications was implemented and evaluated. The first application was developed by using the framework P2PComp, which is directed to building parallel software and its deploy in P2P networks. The second application was developed without the support of this framework and using straightly the communication infrastructure software. Climatic data of the municipality of Lapa, Paraná comprising the period between 1998 and 2007 were used in the experiments. The results demonstrate the feasibility of using parallel computing and P2P networks for executing climate simulations. Best results, measured by the speedup obtained, were observed when using multiple peers (equal to 26) and when executing simulations for a long period of time ( near to 100 years). In such case, the speedup obtained is near to 7.